Thermal structure and sediment bulk density of the MV420 mud volcano on the continental slope of the Canadian Beaufort Sea and its implications for the plumbing system - Kim, Young-Gyun; Jin, Young Keun; Hong, Jong Kuk; Paull, Charles; Caress, David; Jang, ChanHee; So, Byung-Dal (Frontiers in Earth Science, 2022)
The shallow migration path of mudflow of the mud volcano MV420 is investigated in terms of thermal and geotechnical characteristics. MV420 was classified as an active mud volcano that emits methane gas and mud with gas hydrate at a depth of water of 420 m on the continental slope of the Canadian Beaufort Sea. During the summer 2017 IBRV Araon expedition, several measurements of marine heat flow were conducted in the area of juvenile mud mound morphologies identified by multibeam bathymetry and backscatter intensity images obtained by the Monterey Bay Aquarium Research Institute’s autonomous underwater vehicle. The heat probe (a gravity corer with temperature, pressure, and tilt sensors) appeared to reach far below the seafloor to a depth of >70 m, based on pressure readings much higher than the actual water depth. The sediment bulk density in the mudflow migration path of MV420, estimated by pressure change with controlled stretches of a winch cable, was 1.56 g/cm3. The subsurface temperature profiles show that the maximum local temperature ranges from 20 to 40 m below the sea floor, implying substantial vertical variability of geothermal gradients. Our finding of large positive and small negative geothermal gradients above and below the depth of the local temperature maximum, respectively, may represent stagnant hot mud along the mudflow migration path, indicating a pulsative eruption of the mudflow. Gas hydrate is stable only at places out of the path or in a thin layer above the path because of cold bottom water. Furthermore, the thermal conductivity of 0.939 W/m/K and the marine heat flow of 22.5 mW/m2 at a control site outside MV420 is estimated as the background heat flow in the slope, for which little data exists.